The effect of glycerin and polyethylene glycol 400 as humectant on stability and antibacterial activity of nanosilver biosynthetic peel-off mask - Dian Eka Ermawati , Agung Putu Surya, Rini Setyawati, Sukma Uswatun Niswah (Journal of Applied Pharmaceutical Science, 2022)
The peel of sweet orange contains flavonoids and acts as a bioreducer to silver ion, thereby forming nanosilver (AgNPs) that act as an active ingredient in a peel-off mask. Meanwhile, glycerin and polyethylene glycol 400 (PEG 400) are humectants that are possibly combined to control viscosity and keep the skin moist. Therefore, this study aims to determine the effect of combined humectant on the stability and antibacterial activity of the AgNPs peel-off mask. The biosynthesis process was performed by mixing sweet orange peel infusion and silver nitrate solution, after which it was characterized using UV-Vis spectrophotometer, particle size analysis, and Scanning Electron Microscope. Five formulas were made with varying concentrations of humectant during the stability tests of the peel-off mask, and they include organoleptic, viscosity, pH, dry time, and antibacterial activity. Sweet orange peel infusion produces nanosilver with absorption at 440 nm and a particle size of 59.3–64.6 nm, being rod-shaped, and having a strong antibacterial activity. The result of the statistical analysis shows that glycerin-PEG 400 affects viscosity, dry time, and pH. Additionally, a combination of 0.375 and 0.125 g glycerin-PEG 400 showed the best physicochemical stability and had a moderate antibacterial activity after the cycling test compared to another formula.
Keywords: Nanosilver, sweet orange peel, glycerin, polyethylene glycol 400, peel-off mask